2007
DOI: 10.2319/080306-314.1
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Children's Computer-Imaged Facial Profiles by Patients, Mothers and Clinicians

Abstract: Imaging software can be used with children to compare their preferences with those of parents and clinicians to facilitate treatment planning and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…An increased facial convexity was also found in previous cephalometric studies 1,12 for adolescents considered attractive, and preferred by patients and mothers. 25 In the horizontal plane, attractive children and ''young'' adolescents had flatter faces (typical of newborns), but the trend reversed in the ''old'' adolescent subjects, with a relatively more prominent chin. This feature is consistent with current reports on adult male attractiveness 3,15,26 : high prenatal testosterone levels, and high circulating testosterone produce a more prominent lower face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increased facial convexity was also found in previous cephalometric studies 1,12 for adolescents considered attractive, and preferred by patients and mothers. 25 In the horizontal plane, attractive children and ''young'' adolescents had flatter faces (typical of newborns), but the trend reversed in the ''old'' adolescent subjects, with a relatively more prominent chin. This feature is consistent with current reports on adult male attractiveness 3,15,26 : high prenatal testosterone levels, and high circulating testosterone produce a more prominent lower face.…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, esthetics should be evaluated by the laypersons, who actual seek (and finally judge) orthodontic or maxillofacial treatment. 12,23,25 Male and female attractive adolescents were subdivided into groups of different ages, girls being 2-3 years younger than boys. This procedure was made to take the sex-related discrepancies in the timing of pubertal growth spurt into account, 22 thus allowing the assessment of more homogenous biological ages.…”
Section: Discussionmentioning
confidence: 99%
“…O uso de imagens alteradas por software simulando as alterações da face auxilia o diagnóstico e o plano de tratamento entre paciente, pais e cirurgião-dentista, pois se o ortodontista utilizar somente telerradiografia lateral da face como método de diagnósti-co, ele deixará de lado as alterações de tecido mole 13 . A avaliação da estética facial depende muito da percepção de quem e da forma de como se observa.…”
Section: Discussionunclassified
“…[17] One of the main aims of orthodontic treatment is facial esthetics however, the patient's perception of esthetic face depends on the social and cultural rules of the society whereas the orthodontist prefers to use scientifi cally derived Graph 3: Subjects were happy of not happy by their facial profi le (results in %) Graph 1: Distribution of most attractive profi le according to subjects in dental and laypeople group (results in %) Graph 2: Accuracy in profi le judgment by subjects of dental student and laypeople group (results in %) parameters as guideline. [16,[18][19][20] Hence, professional assessment is important, but patient's views about dental appearance should also be respected and included in the assessment for treatment planning. [9] On clinical examination of all the subjects by an orthodontist, it was found that the most common profi le Saudi Arabia population of Riyadh province is convex profi le with a prominent nose.…”
Section: Discussionmentioning
confidence: 99%